The problem accessibility of education in the context of global digitalization: lessons from Armenia - K. A. Aramyan; A. V. Mironov (Вестник университета)
At the turn of the XXIst century, the world entered the Fourth Industrial Revolution, which defined the transition of the human community to a new Digital Era. Digitalization literally reshapes modern societies, their technological and economic structure of states and the international community, the way and nature of social communications, the transfer of information and knowledge. In 2000, UNESCO adopted the Universal Education Agenda for the period from 2015 to 2030, as set out in the Icheon Declaration and the Educa-tion-2030 Framework for Action. The article analyses the situation in the field of education in the Republic of Armenia, as well as indicators that characterize the availability of education and libraries for children in the period from 2015 to 2019.